Cameroon : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Cameroonian authorities found irregularities while implementing the first Poverty Reduction Strategy Paper (PRSP). The process of revising the strategy of PRSP I has resulted in the growth and employment strategy paper (GESP), designed for achieving the MDGs and realizing the vision with multiyear development programs. The GESP deals with a review of development policies, its vision and goals, a growth and employment strategy, state governance and strategic management, macroeconomic and budgetary guidelines, and an institutional framework. The GESP programming and monitoring system thus will help in formulating better policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet